2015
DOI: 10.1590/1678-7067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Cryptosporidium spp. in lambs in the South Central region of the State of São Paulo

Abstract: Considering the proximity of sheep farmers to animals that are possibly diseased or releasing fecal oocysts into the environment and the marked pathogenicity in lambs, the aim of this study was to determine the occurrence and to molecularly characterize the infection by Cryptosporidium spp. in lambs in the South Central region of the state of São Paulo, Brazil. A total of 193 fecal samples were collected from sheep of several breeds, males and females, aged up to one year. Polymerase chain reaction (nested-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(25 reference statements)
1
8
0
3
Order By: Relevance
“…Previously, it was known as C. bovis-like and was found in sheep in the United States (SANTÍN et al, 2007), Spain (NAVARRO-I-MARTINEZ et al, 2007), Tunisia CHALMERS, 2008), United Kingdom (MUELLER-DOBLIES et al, 2008), China (WANG et al, 2010;YE et al, 2013), Norway (ROBERTSON et al, 2010), Australia (SWEENY et al, 2011), andEgypt (MAHFOUZ et al, 2014). In Brazil, the first report of this parasite in sheep was recorded in São Paulo in 2015, where it was found infecting 5-to 360-day-old sheep (ZUCATTO et al, 2015). In this study, the protozoa were found in adult sheep of approximately 3 years of age.…”
Section: Resultssupporting
confidence: 48%
See 3 more Smart Citations
“…Previously, it was known as C. bovis-like and was found in sheep in the United States (SANTÍN et al, 2007), Spain (NAVARRO-I-MARTINEZ et al, 2007), Tunisia CHALMERS, 2008), United Kingdom (MUELLER-DOBLIES et al, 2008), China (WANG et al, 2010;YE et al, 2013), Norway (ROBERTSON et al, 2010), Australia (SWEENY et al, 2011), andEgypt (MAHFOUZ et al, 2014). In Brazil, the first report of this parasite in sheep was recorded in São Paulo in 2015, where it was found infecting 5-to 360-day-old sheep (ZUCATTO et al, 2015). In this study, the protozoa were found in adult sheep of approximately 3 years of age.…”
Section: Resultssupporting
confidence: 48%
“…It was detected in sheep in Australia (SWEENY et al, 2011;RYAN et al, 2005;YANG et al, 2009), United States (SANTÍN;FAYER, 2007;SANTIN et al, 2007), Belgium (GEURDEN et al, 2008), China (WANG et al, 2010), Spain (DIAZ et al, 2010), Norway (ROBERTSON et al, 2010), UK (ELWIN;CHALMERS, 2008;MUELLER-DOBLIES et al, 2008), and other countries. In Brazil, this species of Cryptosporidium has been detected by Fiuza et al (2011) in the State of Rio de Janeiro and by Silva et al (2014) and Zucatto et al (2015) in São Paulo. Zucatto et al (2015) found this species in 5-to 180-day-old sheep, however in this study it was found in a sheep approximately 2.5 years old.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Similar prevalence values were observed in previous studies, as in Paz e Silva et al (2014) Cryptosporidium spp. is a parasite that may infect humans, therefore an important international public health matter (Zucatto et al, 2015). In a previous research developed in Poland with 159 sheep, 16 animals were found parasitized by oocysts of Cryptosporidium using the Ziehl-Neelsen modified method (Majewska et al, 2000).…”
Section: Resultsmentioning
confidence: 99%